PEMBELAJARAN AL-QURAN HADITS PADA STANDAR KOMPETENSI LULUSAN SEKOLAH ISLAM TERPADU AL-FITYAH - Wulandari, Putri; Nasution, Siti Zahara Khairunnisah; Azhara, Siti; Nasution, Siti Kholijah; Nurhalisah, Siti; Ramadhani, Putri (Jurnal Generasi Tarbiyah: Jurnal Pendidikan Islam, 2023)
ABSTRACT Al-Qur'an Hadith learning is two different lesson content, but in terms of nomenclature this learning becomes one name of learning, namely Al-Qur'an Hadith. In the Integrated Islamic School education unit, there is no specific nomenclature of Al-Qur'an Hadith subjects, only Islamic Religious Education (PAI) learning. But that doesn't mean the Integrated Islamic School doesn't study the Al-Qur'an Hadith. They still study it, it's just that the scope is narrower than students who are in Madrasas, and their learning is more emphasized on the habituation of Islamic manners and morals in accordance with the Al-Quran and Hadith. This study aims to determine the need for the implementation of Al-Qur'an Hadith in Integrated Islamic-based schools, namely to create schools that effectively develop educational processes that can develop the natural potential of students towards the vision of forming a generation that is pious and has the character of a leader based on a philosophy that refers to the messages of Islamic education as stated in the Qur'anul Karim. This research uses a type of descriptive qualitative approach, that is, a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. From research conducted at the Alfityah Integrated Islamic School, it can be concluded that even though the Al-Quran Hadith subject is not part of the school curriculum, it does not mean that the school does not apply the main points of the lessons contained in it. But by way of direct application it is more needed for the provision of students in their daily lives.